Heterologous Expression of Serine Hydroxymethyltransferase-3 From Rice Confers Tolerance to Salinity Stress in E. coli and Arabidopsis - Mishra, Pragya; Jain, Ajay; Takabe, Teruhiro; Tanaka, Yoshito; Negi, Manisha; Singh, Nisha; Jain, Neha; Mishra, Vagish; Maniraj, R.; Krishnamurthy, S. L.; Sreevathsa, Rohini; Singh, Nagendra K.; et al. (Frontiers in Plant Science, 2019)
Among abiotic stresses, salinity stress adversely affects growth and development in rice. Contrasting salt tolerant (CSR27), and salt sensitive (MI48) rice varieties provided information on an array of genes that may contribute for salt tolerance of rice. Earlier studies on transcriptome and proteome profiling led to the identification of salinity stress-induced serine hydroxyl methyltransferase-3 (SHMT3) gene. In the present study, SHMT3 gene was isolated from salt-tolerant (CSR27) rice. The functional characterization of OsSHMT3 from salt-tolerant OsSHMT3 exhibited salinity-stress induced accentuated and differential expression levels in different tissues of rice. OsSHMT3 was overexpressed in E. coli and assayed for enzymatic activity and modelling protein structure. Further, Arabidopsis transgenic plants overexpressing OsSHMT3 exhibited tolerance towards salinity stress. Comparative analyses of OsSHMT3 vis a vis wild type by ionomic, transcriptomic and metabolic profiling, protein expression and analysis of various agronomic traits revealed a pivotal role of OsSHMT3 in conferring tolerance towards salinity stress. The gene can further be used in developing gene based markers for salinity stress to be employed in marker assisted breeding programs.